Kajian Pelaksanaan Penyuluhan dan Partisipasi Perempuan pada Kegiatan Pertanian Tanaman Palawija di Desa Suka Damai, Kecamatan Dramaga, Kabupaten Bogor - Hayati Zakaria (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2013)
The study of the implementation studies of extension and women's participation in Agricultural Crops Activity in Sukadamai Village, District Dramaga, Bogor Regency aimed to analyze the level of women participation in agricultural crops activity; to analyze the level of women participation in agricultural crops extension activities; to identify the institusional of agricultural extension; to analyze the influence factor in the ability of the extension worker to improve women's participation in agricultural crops extension activities. Sampling was done randomly respondents. Number of study sample as many as 30 people. Primary data obtained through the use of closed questionnaires, interviews with the use of an open questionnaire, focus group discussion (FGD), and observations. Stages of data analysis is divided into stages of data description and hypothesis testing phase. Results showed that the women participation in agricultural crops extension activities in high category is 53,3%; the women participation in agricultural extension activities in the low category is 50%; the existence of agricultural extension workers is recognized by women are civil servants extension workers and independent extension workers; the method of agricultural extension and the attidude of extension workers affect significantly (p < 0,05) to women's participation in agricultural extension activities.Keywords: participation, agricultural extension, agricultural crops activity, the institusional of agricultural extension